ANALISIS SISTEM INTEGRASI SAPI DAN KELAPA SAWIT DALAM MENINGKATKAN PENDAPATAN PETANI DI KABUPATEN LABUHANBATU - Poltak Sirait; Zulkifli Lubis; Murbanto Sinaga (JURNAL AGRICA, 2018)
Analysis of Integration System of Cow And Oil Palm In Increasing Farmers Income In Labuhanbatu District ". Kabupten Labuhanbatu was chosen as the location in this study on the grounds that this district is a center of palm oil production and cattle breeding center in North Sumatra. Kecamatan Sampel selected sub district Bilah Hulu, Bilah Hilir and Pangkatan because as a center of production of palm oil and cattle in Labuhanbatu regency. This research used field observation method using questionnaire and interview instrument, this research type is descriptive quantitative. The population in this study was 78 oil palm farmers/ranchers selected randomly. The sample consists of 44 oil palm farmers without integration with saip and 34 palm oil farmers with integration with cows. Data analysis model used is descriptive and quantitative analysis. To test the difference of farmer's income, it is used the mean difference test (t test) and to analyze the factors influencing the farmer's income is used Multiple Linear Regression Analysis with the help of SPSS software version 17. Result of research: There is a very significant difference of income level between farmers who implement and farmers who have not implemented a system of cattle and oil palm integration in the research area. The income difference is Rp. 7.87 Million / Year. Educational factors, farm experience and the number of family dependents have no significant effect on farmers' income. While the factor of farming system and land area have a very significant effect to farmer's income. Keywords: Palm oil, cattle, integration, forage, waste, income, education, farming system